2021
DOI: 10.1002/ccr3.4918
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up of two cases of suspected interstitial lung disease following severe COVID‐19 infection shows persistent changes in imaging and lung function

Abstract: Physicians are observing persisting symptoms and unexpected organ dysfunction after severe COVID‐19. In this report, we present the follow‐up of two cases of suspected interstitial lung disease following the viral infection. Up to the last month of follow‐up, both patients presented with persistent changes in imaging and pulmonary function tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Post-acute COVID-19 syndrome (PACS) is present in more than half of patients, even after 2 years of acute disease [ 1 , 3 , 6 ]. Fatigue and dyspnea are the most common manifestations [ 1 , 7 ]. Current literature has described the most common effects of SARS-CoV-2 on lung structure and function as altered diffusion capacity and restrictive and obstructive patterns [ 6 ]; however, little is known about the role of SAD.…”
Section: Discussionmentioning
confidence: 99%
“…Post-acute COVID-19 syndrome (PACS) is present in more than half of patients, even after 2 years of acute disease [ 1 , 3 , 6 ]. Fatigue and dyspnea are the most common manifestations [ 1 , 7 ]. Current literature has described the most common effects of SARS-CoV-2 on lung structure and function as altered diffusion capacity and restrictive and obstructive patterns [ 6 ]; however, little is known about the role of SAD.…”
Section: Discussionmentioning
confidence: 99%
“…The British Thoracic Society (BTS) guide suggests evaluating patients with severe COVID-19 with full PFTs 12 weeks after hospital discharge [ 62 ]. According to the findings of Cherrez-Ojeda, the impairment in PFTs appears to persist well beyond this timeframe [ 63 ]. A prospective observational study that analyzed the evolution of functional and radiological features between 3 and 6 months after hospital discharge in critical COVID-19 survivors reported the persistence of functional abnormalities such as impairments in total lung capacity (TLC) (41% and 33%) and DLCO (88% and 80%) at the end of the monitoring period [ 64 ].…”
Section: Pulmonary Function Testsmentioning
confidence: 99%
“…Cherrez et al [7] have reported the follow-up of two cases of pulmonary fibrosis after severe COVID-19 infection. One year later, both cases maintained symptoms of shortness of breath upon exertion and persistence of ground-glass-type opacities, traction bronchiectasis, and interlobular septal thickening that covered much of the lung parenchyma (Figure 1A,B).…”
Section: Pathophysiologymentioning
confidence: 99%
“…However, to our knowledge, there are no prevalence studies of post-COVID-19 pulmonary fibrosis (PCPF) in Latin America. Diagnosis involves persistent respiratory symptoms accompanied by abnormalities in pulmonary function tests and imaging results from serial chest computed tomography [7,8]. No fully proven options are available for the treatment of PCPF.…”
Section: Introductionmentioning
confidence: 99%